Vagus Nerve Stimulation Attenuates Cerebral Microinfarct and Colitis-induced Cerebral Microinfarct Aggravation in Mice - Chen, Xiaofeng; He, Xiaofei; Luo, Shijian; Feng, Yukun; Liang, Fengyin; Shi, Taotao; Huang, Ruxun; Pei, Zhong; Li, Zhendong (Frontiers in Neurology, 2018)
Cerebral cortical microinfarct (CMI) is common in patients with dementia and cognitive decline. Emerging studies reported that intestinal dysfunction influenced the outcome of ischemic stroke and that vagus nerve stimulation (VNS) protected against ischemic stroke. However, the effects of intestinal dysfunction and VNS on CMI are not clear. Therefore, we examined the influence of colitis and VNS on CMI and the mechanisms of VNS attenuating CMI in mice with colitis. CMI was induced using a two-photon laser. Colitis was induced using oral dextran sodium sulfate (DSS). The cervical vagus nerve was stimulated using a constant current. In vivo blood-brain barrier (BBB) permeability was evaluated using two-photon imaging. Infarct volume, microglial and astrocyte activation, oxidative stress and proinflammatory cytokine levels were assessed using immunofluorescent and immunohistochemical staining. The BBB permeability, infarct volume, activation of microglia and astrocytes and oxidative stress increased significantly in mice with colitis and CMI compared to those in mice with CMI. However, these processes were reduced in CMI mice when VNS was performed. Brain lesions in mice with colitis and CMI were significantly ameliorated when VNS was performed during the acute phase of colitis. Our study demonstrated that VNS alleviated CMI and this neuroprotection was associated with the suppression of BBB permeability, neuroinflammation and oxidative stress. Also, our results indicated that VNS reduced colitis-induced microstroke aggravation.